G60(P) Red flags: parent-reported earliest concerns regarding their child's emerging cerebral palsy. (25th October 2020) - Baggaley, J; Rapley, T; Basu, A
Abstract : Background: Each year around 1800 UK children are diagnosed with Cerebral Palsy (CP). Of these, 40–50% are deemed 'low risk' at birth and therefore rely on their parents and primary care health professionals (HCPs) to identify concerning features and seek early referral. Some parents report difficulties in communicating their concerns, and being falsely reassured. Aims: To describe the nature of the earliest concerns parents report to HCPs in children with emerging CP. Methods: Parents of children with CP were recruited via social media to take part in an, ethically approved, online survey. This collected information on child and respondent demographics and the earliest concerns parents had regarding their child's development. Thematic analysis was undertaken on the first 200 responses. Results: Four responses were excluded due to ineligibility. Most responses (n=186) were from mothers. Children with Hemiplegic CP made up 51.5% of the sample (table 1 ). Eight main themes emerged; Developmental Milestones (n=141), Atypical Movements ('His left leg did not kick excitedly in the bath') (n=97), Worrying Birth History (n=86), Posture (n=69), Tone (n=48), Feeding (n=23), Temperament (including sleep)(n=22), and Parental Intuition ('I just knew something wasn't right.')(n=16). Conclusion/Discussion: Developmental Milestones were the most frequently reported concern, supporting current screening processes. However, this represented only 28% of the total concern burden. Although some concerns were non-specific, a proportion of concerns in all categories were not acted on. Limitations: Retrospective nature; lack of clinician confirmation of clinical details. Strengths: Potential to further mine responses to identify parental concerns not acknowledged by HCPs, as potential new 'red flags'. Such data could improve early recognition and referral of infants with emerging CP.